KEBIJAKAN HUKUM PIDANA (PENAL POLICY) PERAMPASAN ASET (ASSET RECOVERY) HASIL TINDAK PIDANA DALAM HUKUM POSITIF INDONESIA - , ISKA DANIATI, Prof. Dr. Edward Omar Sharif Hiariej, S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the history of human life, the kind of crime is not fixed. Crime or criminal offense is a form of \"deviant behavior\" is always there and is attached to each form of society, there is no society devoid of crime. Can be ascertained in a criminal act requires a tool, or instrument used, both as a means and measures, as well as a destination. Crime also raises a variety of benefits for the perpetrators, especially the economic benefits in the form of wealth. Efforts are most effective in the eradication and prevention of such offenses other than just dropping the body against the perpetrators of criminal offenses is to kill the \"life\" of the crime itself, namely by seizing the proceeds and instruments of the crime, in other words perpetrators found and convicted criminal and the crime proceeds and instruments seized and confiscated by the State. Based on the title and the background of the case above, then it can be formulated two questions namely